Pengaruh Electronic-Word of Mouth dan Electronic-Service Quality terhadap Electronic-Repurchase Intention pada PT Rosalia Indah Transport - Gamastri Duary; Handjojo Djoko Waloejo; Dinalestari Purbawati (Jurnal Ilmu Administrasi Bisnis, 2023)
The number of new bus companies that have emerged has made otobus entrepreneurs compete to win the competition, one of which is by creating an online ticketing system that will make it easier for customers to order tickets. To get a high intensity of electronic-repurchase, one way is to maintain good electronic-word of mouth and electronic-service quality. High electronic repurchase intention can be influenced by electronic-word of mouth and good electronic-service quality in accordance with customer expectations. In fact, not all bus companies have good electronic-word of mouth and electronic-service quality, including PT Rosalia Indah Transport. This type of research is explanatory research with purposive sampling method. The data collection technique used was by distributing questionnaires to 100 respondents who had purchased Rosalia Indah online tickets at least 2 times in the last 3 months. The data analysis method in this study used SPSS version 25. The results in this study indicate that there is a positive influence between the electronic-word of mouth variable on electronic-repurchase intention, then there is a positive influence between the electronic-service quality variable on electronic-repurchase intention, and there is a positive influence between the electronic-word of mouth and electronic-service variables. quality on electronic-repurchase intention.Banyaknya perusahaan bus baru yang muncul membuat pengusaha otobus berlomba memenangkan persaingan, salah satunya dengan membuat sistem online ticketing yang akan memudahkan pelanggan untuk pemesanan tiket. Untuk mendapatkan intensitas pembelian ulang secara electronic- yang tinggi, salah satu caranya dengan menjaga electronic-word of mouth dan electronic-service quality dengan baik. Electronic-repurchase intention yang tinggi dapat dipengaruhi oleh electronic-word of mouth dan electronic-service quality yang baik sesuai dengan harapan pelanggan. Kenyataannya, tidak semua perusahaan otobus memiliki electroninc-word of mouth dan electronic-service quality yang baik, termasuk PT Rosalia Indah Transport. Tipe penelitian ini, yaitu explanatory research dengan metode purposive sampling. Teknik pengumpulan data yang digunakan dengan menyebarkan kuesioner kepada 100 responden yang pernah melakukan pembelian tiket Rosalia Indah secara online minimal 2 kali dalam 3 bulan terakhir. Metode analisis data dalam penelitian ini menggunakan SPSS versi 25. Hasil dalam penelitian ini menunjukkan terdapat pengaruh positif antara variabel electronic-word of mouth terhadap electronic-repurchase intention, lalu terdapat pengaruh positif antara variabel electronic-service quality terhadap electronic-repurchase intention, serta terdapat pengaruh positif antara variabel electronic-word of mouth dan electronic-service quality terhadap electronic-repurchase intention.